Percepções da influência das atividades extracurriculares durante uma trajetória acadêmica - Curcelli, Emilio Martins (Universidade Federal de São Carlos, 2020)
The course conclusion work (TCC) is a mandatory instrument to graduate in medicine from the Federal University of São Carlos (UFSCar). According to the pedagogical project1, the work should present the student's perception of “analyzing the individual capacity of the student to synthesize his education trajectory, considering the dimensions of teaching, assistance and research”. The UFSCar medical course, created in 2005, with a total workload of 9620 hours, has an active methodology with an integrated, constructivist and competence-oriented curriculum, seeking a more active and reflective participation of the student, while bringing theory closer with practice from the beginning. The course is structured in three educational cycles: Comprehensiveness of care I (first and second academic years); integrality of care II (third and fourth academic years) and integrality of Care III (fifth and sixth academic years, or boarding school). Through this organization, it is expected, at the end of the course, that the student will have competence within the three main areas: health (care for individual health needs and care for collective health needs), Management (organization of health work and health management). care) and education1. Extracurricular activities (AEC), also called complementary activities, include participation or organization in scientific events such as congresses and symposium, monitoring, study groups, academic leagues, scientific initiation, extension projects, paid or unpaid internships, cultural and social activities, among others2. The literature is vast in relation to students' motivation to pursue such activities, such as: going deeper into a specific topic, helping socializing with other students, bringing theory and practice together and complementing the basic curriculum. Participating in such AEC also correlated with several gains for the student, such as: academic / professional gains (higher performance, improvement of technical skills, lower dropout, greater professional satisfaction), cultural and social gains (such as improvement of leadership and interpersonal relationships, improvement in understanding of society, gain in humanity, approximation with different cultures) and psychological gains (serving as a strategy to protect against burnout) 2-5. Bearing in mind that, during the author's individual trajectory in the course, there was contact with diversified AEC, the study sought to analyze, in a self-critical manner and based on scientific evidence, how these activities could influence graduation and contribute to professional training, particularly in medical practice. As a secondary objective, we sought to reflect what were the motivations that led to carry out such AEC.
Perceptions of the influence of extracurricular activities during an academic trajectory
Keywords: Saúde; Educação; Gestão; Currículo; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA